Alternatives to the central bank in the developing world - Collyns, Charles (Washington, D.C. : International Monetary Fund, 1983)
This paper surveys the alternative institutional forms that have emerged and seeks to explain the observed diversity of experience
"July 1983."
Bibliography: p. 23.
osc 16/05/2018
Loans
Keywords: Banks and banking, Central; Monetary policy